2013
DOI: 10.1111/ggi.12049
|View full text |Cite
|
Sign up to set email alerts
|

Pain and hospice care in nursing home residents with dementia and terminal cancer

Abstract: Aim One condition associated with severe end-of-life pain that can lead to a poor quality of death is cancer. Cancer pain in people with dementia is of particular concern because of communication problems that occur with worsening disease. The aim of the current pilot study was to examine the association between hospice enrolment, dementia severity and pain among nursing home residents who died from advanced cancer. Methods Between-groups cross-sectional chart audits of 55 nursing home residents with dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 38 publications
3
70
0
Order By: Relevance
“…3 Thus, occurrence of pain and dementia will both increase with age, 46 presenting challenges for pain assessment in both long-term care and adult critical care. Cognitively impaired individuals report pain less frequently and receive minimal 7 to no pain medication, 8 even when there is a known condition that causes pain, such as cancer. 7 Pain at rest in the intensive care unit (ICU) is common in adult patients and contributes to complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thus, occurrence of pain and dementia will both increase with age, 46 presenting challenges for pain assessment in both long-term care and adult critical care. Cognitively impaired individuals report pain less frequently and receive minimal 7 to no pain medication, 8 even when there is a known condition that causes pain, such as cancer. 7 Pain at rest in the intensive care unit (ICU) is common in adult patients and contributes to complications.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although multiple tools exist to help assess pain in dementia, 6,10,11 pain remains under assessed and inadequately treated. 8,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Earlier enrollment in Hospice is associated with an increased likelihood of receiving an opioid (80% vs 43%) and should be considered. 18 Hospital systems should consider applying pain and behavioral management protocols to address this problem in an attempt to standardize care and enhance end-of-life treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pain and painful conditions among NH residents has remained unchanged over the last two decades, with most studies reporting pain prevalence in nursing homes as greater than 50 percent (Leong & Nuo, 2007; Smalbrugge, Jongenelis, Pot, Beekman, & Eefsting, 2007; Weiner, Peterson, Ladd, McConnell, & Keefe, 1999; Won et al, 2004). Although documentation of pain is now required as the 5 th vital sign among NH residents (Fishman, 2005), pain commonly occurring in this population remains undertreated (Monroe & Carter, 2010; Monroe, Carter, Feldt, Dietrich, & Cowan, 2013; Monroe, Herr, Mion, & Cowan, 2013; Monroe & Mion, 2012). For example, despite cancer being a cause of severe pain among NH residents (Monroe, Carter, et al, 2013), a seminal study found that 26 percent of NH residents (N=13,625) with daily cancer pain did not receive any pain medication (Bernabei et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although documentation of pain is now required as the 5 th vital sign among NH residents (Fishman, 2005), pain commonly occurring in this population remains undertreated (Monroe & Carter, 2010; Monroe, Carter, Feldt, Dietrich, & Cowan, 2013; Monroe, Herr, Mion, & Cowan, 2013; Monroe & Mion, 2012). For example, despite cancer being a cause of severe pain among NH residents (Monroe, Carter, et al, 2013), a seminal study found that 26 percent of NH residents (N=13,625) with daily cancer pain did not receive any pain medication (Bernabei et al, 1998). Similarly, another study showed that among 411 hospitalized older adults with acute hip fracture, half complained of moderate to severe pain at rest, and four out of five complained of pain during movement, yet 87 percent did not have a standing order for pain medicine (Morrison et al, 2003).…”
Section: Introductionmentioning
confidence: 99%